DEVELOPMENT OF TEACHER COMPETENCIES AND WELFARE IN THE DIGITAL ERA: HUMAN RESOURCE MANAGEMENT STRATEGIES IN SCHOOLS - Dasep Supriatna (International Journal of Teaching and Learning, 2025)
This study investigates human resource management strategies to enhance teacher competencies and welfare in the digital era, utilizing frameworks such as Human Capital Theory[1], Self-Determination Theory[2], Transformational Leadership[3], Organizational Support, and Emotional Intelligence. Employing a mixed-methods approach, the research evaluates professional development programs, welfare initiatives, and leadership practices across diverse school contexts. Results reveal significant improvements in digital literacy, emotional intelligence, and job satisfaction, alongside challenges in resource allocation and sustainability. Findings underscore the need for holistic, equitable strategies to foster adaptive and resilient educational environments.